1997
DOI: 10.1111/j.1469-8986.1997.tb01739.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation, affect, and aerobic exercise: An examination of both state‐independent and state‐dependent relationships

Abstract: Resting electroencephalograph (EEG) asymmetry is a biological marker of the propensity to respond affectively to, and a measure of change in affect associated with, acute aerobic exercise. This study examined the EEG-affect-exercise relationship. Twenty participants performed each of three randomly assigned 30-min conditions: (a) a nonexercise control, (b) a cycling exercise at 55% VO2max, and (c) a cycling exercise at 70% VO2max. EEG and affect were assessed pre- and 0, 5, 10, 20, and 30 min postcondition. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…It has been shown repeatedly that exercise can reduce anxiety symptoms in healthy adults (Hale & Raglin, 2002), in anxious women (Breus & O'Connor, 1998), and in psychiatric patients (Broocks et al, 1998). The anxiolytic effect of exercise was connected with an activation of the left frontal brain regions (Petruzzello & Tate, 1997), with an exercise-induced increased serotonin turnover in the mediobasal hypothalamus (Broocks, Schweiger, & Pirke, 1991), and with a down-regulation of 5-HT-2c receptors in certain brain regions (Broocks et al, 2001). Furthermore, it is well known that repetitive behavior helps to filter out both extraneous stimuli and disruptive affect-laden cognitions (Rauch & Savage, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown repeatedly that exercise can reduce anxiety symptoms in healthy adults (Hale & Raglin, 2002), in anxious women (Breus & O'Connor, 1998), and in psychiatric patients (Broocks et al, 1998). The anxiolytic effect of exercise was connected with an activation of the left frontal brain regions (Petruzzello & Tate, 1997), with an exercise-induced increased serotonin turnover in the mediobasal hypothalamus (Broocks, Schweiger, & Pirke, 1991), and with a down-regulation of 5-HT-2c receptors in certain brain regions (Broocks et al, 2001). Furthermore, it is well known that repetitive behavior helps to filter out both extraneous stimuli and disruptive affect-laden cognitions (Rauch & Savage, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…EEG channels of interest were left and right frontal regions (F3, F4). While measures of posterior sites (e.g., parietal) would further allow determination of the regional specificity of any EEG effects, numerous EEG-exercise-affect studies have examined posterior scalp sites and revealed no significant alterations after exercise engagement beyond the anterior sites (Petruzzello and Tate, 1997;Petruzzello et al, 2001;Hall et al, 2007). Thus, with limited EEG channels available, the present study focused on the essential frontal sites.…”
Section: Eeg Recording and Data Analysismentioning
confidence: 95%
“…A number of studies have revealed that acute exercise does impact frontal EEG alpha asymmetry and that resting frontal EEG alpha asymmetry is predictive of the affective state following exercise (Petruzzello and Landers, 1994;Petruzzello and Tate, 1997;Petruzzello et al, 2001, Hall et al, 2007. However, none of these investigations examined the impact of exercise duration on this measure.…”
Section: Introductionmentioning
confidence: 94%
“…Electroencephalography (EEG) is a valuable tool used to assess electrophysiological changes associated with mental illness, and has shown increasing utility in assessing brain function in clinical studies of depression (17,18). The effects of exercise on the reduction of mood symptoms are observed by analyzing cortical hemispherical activity (19)(20)(21)(22)(23), especially in the alpha band (8)(9)(10)(11)(12)(13). Based on Davidson's hypothesis (24), cortical asymmetry observed through the EEG is associated with emotion, with positive affects being related to greater left frontal activity and negative affects to greater right frontal activity.…”
Section: Introductionmentioning
confidence: 99%